1997
DOI: 10.1016/s0014-5793(97)01314-8
|View full text |Cite
|
Sign up to set email alerts
|

Glucose regulates the promoter activity of aldolase A and pyruvate kinase M2 via dephosphorylation of Sp1

Abstract: Proliferating cells and tumour cells maintain a high glycolytic rate even under aerobic conditions. FT02B cells, a rat hepatoma cell line, show high activities of glycolytic enzymes. Within a culture period of 48 h the cell number increases 5-fold. Replacement of glucose by pyruvate in the culture medium lowers glycolytic enzyme activity and prevents proliferation. Transfection assays revealed that glucose deprivation dramatically decreases the transcriptional activities of the Spl-dependent aldolase and pyruv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
52
2
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 25 publications
6
52
2
1
Order By: Relevance
“…Moreover, PP2A, but not PP1, enhanced the IL-2-driven up-regulation of Sp1 site-mediated transcriptional activity. In contrast to our data, PP1 has been implicated in glucose-induced dephosphorylation of Sp1 (39,40). The latter studies, however, did not determine whether PP1 physically interacted with Sp1, and it is conceivable that the enzyme acts upstream of a PP2A/Sp1 signaling complex.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, PP2A, but not PP1, enhanced the IL-2-driven up-regulation of Sp1 site-mediated transcriptional activity. In contrast to our data, PP1 has been implicated in glucose-induced dephosphorylation of Sp1 (39,40). The latter studies, however, did not determine whether PP1 physically interacted with Sp1, and it is conceivable that the enzyme acts upstream of a PP2A/Sp1 signaling complex.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, increased phosphorylation either enhances (6,64) or inhibits Sp1 DNA binding and transactivation (65). Conversely, dephosphorylation can increase both activities (38,40). These discrepancies most likely illustrate the fact that Sp1 regulation has been analyzed at different stages of cell growth and differentiation and that multiple triggering signals and cell types have been used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sp1 stimulates cAMPdependent transcriptional stimulation from the CYP11A gene promoter in SL2 cells (52). However, it has been reported that the phosphorylated and the nonreduced form of Sp1 showed a decrease in binding to a DNA fragment that contained both GC boxes 1 and 2 of the PKM gene (51,53). On the other hand, cdc25C gene transcription, which occurs late in the S/G 2 phase, is regulated by a cell cycle-dependent repressor element and an upstream activating sequences which contains three CCAAT motifs and two Sp1-binding sites.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that the DNA binding activity of Sp1 can be modulated either positively or negatively by phosphorylation [37][38][39] . For glucose-responsive genes, a glucose-dependent Sp1 dephosphorylation has been suggested to be responsible for glucose-mediated activation of the aldolase A gene 40 . We have found that glucose treatment increases phosphorylation of MAP kinases P38 and P44/42, and thus induces phosphorylation of the existing Sp1 protein without changing the amount of total Sp1 protein.…”
Section: Discussionmentioning
confidence: 99%